Comparative between Syndromic and Nonsyndromic Craniosynostosis: A Literature Review - Rasyid, Fahmi; Mouza, Abdurrahman (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Craniosynostosis (CS) refers to the premature fusion in the perinatal stage of one or multiple skull sutures, also denominated synostoses (sagittal, metopic, uni and bilateral coronal, and lamboidal), which are commonly accompanied by facial, trunk, and limb deformities. During normal human body and head development, cranial growth achieves approximately 80% of the adult size at birth and its definitive size between 2.5 and 3 years of age. In the fetal or newborn skull, the flat bones are separated by four fontanelles and six major cranial sutures that participate in this process. Hereby presented the literature review of syndromic and non-syndromic craniosynostosis.